Perlindungan Hukum terhadap Tanah Ulayat Masyarakat Adat yang Masuk Ke dalam Pembangunan Ibu Kota Negara - Miftah, Farrah (Wajah Hukum, 2024)
This research examines the legal protection of customary lands of indigenous communities involved in the development of special economic zones (IKN). This research uses a legal approach and case studies to analyze the impact of IKN development on the customary rights of indigenous communities. The results of this research highlight the challenges associated with IKN development and potential violations of customary land rights. This study also reviews the existing legal framework and recommends improving and strengthening legal protection for indigenous peoples. Therefore, this study contributes to a deeper understanding of the dynamics of legal protection of customary land in the changing IKN development environment and highlights the importance of supporting the rights of indigenous peoples for sustainable development.